INCREASING THE EFFICIENCY OF SILICON SOLAR CELLS THROUGH ANTIREFLECTIVE TiO2 WITH THE SPIN COATING METHOD - Alfiatul Ma'arifah; Markus Diantoro; Norazlin Norazlin; Herlin Pujiarti (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2026)
In this study, the efficiency of silicon solar cells is enhanced by using a titanium dioxide (TiO₂) anti-reflective (AR) coating. The use of the TiO₂ AR coating aims to reduce recombination at the solar cell interface. Many researchers have developed TiO₂ AR coating using the spin coating method. However, research with variations in spin coating speed has not yet been studied. Based on the UV-DRS results, the minimum reflectance was obtained in the sample with the lowest spin coating speed. Low reflectance indicates that more photons reach and are absorbed by the silicon. These results were confirmed by the results of the I-V test that had been carried out at the lowest spin coating speed, resulting in the highest Jsc of 135.4 mA/cm² and a maximum efficiency of 20.7%. This high Jsc can be attributed to maximum photon absorption, thereby increasing efficiency. The EIS results also showed that the highest recombination resistance of 836.4 Ω was obtained for the lowest spin coating speed variation. Where recombination was successfully suppressed with the increase in Rrec obtained in this study.